Znaczenie gazu ziemnego w relacjach polsko-amerykańskich - Sienkiewicz, Marcin (Instytut Studiów Międzynarodowych Uniwersytetu Wrocławskiego, 2017)
The article is devoted to the subject of natural gas in the current relations between Poland and the United States. The subject was chosen partly because of the growing significance of natural gas in the economic strategies of both countries. Natural gas is one of the most important resources traded internationally. Concrete cases of cooperation in the field, supported by declarations on the highest political levels, allow us to assume the existence of a high potential for the Polish-American cooperation in the area of natural gas trade and supply, as well as common economic and political interests connected with this resource.
Keywords: natural gas; LNG; Poland; the USA; the European Union; Gazprom; Russia; Central and Eastern Europe; gas hub; diversification; Trimarium